Current Situation and Reflections of Environmental Accounting Information Disclosure in China’s Iron and Steel Industry under the Background of "Double Carbon" - Deng, Lingfeng (Pacific International Journal, 2022)
China plans to reach peak carbon use by 2030 and achieve carbon neutrality by 2060. This "double carbon" target makes the iron and steel industry, a high-consumption, heavy-polluting, energy-intensive industry, face great challenges. In order to achieve green transformation and promote sustainable development, the iron and steel industry, as a national pillar industry, should raise awareness of environmental protection, increase environmental accounting information disclosure, and improve the level of environmental accounting information disclosure. This paper discusses the current situation of environmental accounting information disclosure in the iron and steel industry, summarizes the current problems of environmental accounting information disclosure in the iron and steel industry, and proposes countermeasures to solve them. It is found that the iron and steel industry currently has problems such as low initiative of environmental information disclosure, less disclosure of negative information, scattered disclosure information, non-uniform disclosure carriers, etc. It is recommended to accelerate the construction of the environmental accounting disclosure system and regulations, improve and standardize the environmental accounting information disclosure system, strengthen the construction of third-party audit, improve the awareness of environmental information disclosure of enterprises, and standardize the environmental accounting information disclosure from both national and enterprise levels Content.